Maternal symptoms of depression and sensitivity mediate the relation between maternal history of early adversity and her child temperament: The inheritance of circumstance. (May 2020) - Bouvette-Turcot, Andrée-Anne; Fleming, Alison S.; Unternaehrer, Eva; Gonzalez, Andrea; Atkinson, Leslie; Gaudreau, Hélène; Steiner, Meir; Meaney, Michael J.
Abstract: We examined maternal depression and maternal sensitivity as mediators of the association between maternal childhood adversity and her child's temperament in 239 mother–child dyads from a longitudinal, birth cohort study. We used an integrated measure of maternal childhood adversity that included the Childhood Trauma Questionnaire and the Parental Bonding Index. Maternal depression was assessed with the Edinburgh Postnatal Depression Scale at 6 months postpartum. Maternal sensitivity was assessed with the Ainsworth maternal sensitivity scales at 6 months. A measure of "negative emotionality/behavioral dysregulation" was derived from the Early Childhood Behaviour Questionnaire administered at 36 months. Bootstrapping-based mediation analyses revealed that maternal depression mediated the effect of maternal childhood adversity on offspring negative emotionality/behavioral dysregulation (95% confidence interval [0.026, 0.144]). We also found a serial, indirect effect of maternal childhood adversity on child negative emotionality/behavioral mediated first by maternal depression and then by maternal sensitivity (95% confidence interval [0.031, 0.156]). Results suggest the intergenerational transmission of the effects of maternal childhood adversity to the offspring occurs through a two-step, serial pathway, involving maternal depression and maternal sensitivity.